Inactivation of highly transmissible livestock and avian viruses including influenza A and Newcastle disease virus for molecular diagnostics - Welch, Jennifer L.; Shrestha, Ram; Hutchings, Heather; Pal, Narinder; Levings, Randall; Robbe-Austerman, Suelee; Palinski, Rachel; Shanmuganatham, Karthik K. (Frontiers in Veterinary Science, 2024)
There is a critical need for an inactivation method that completely inactivates pathogens at the time of sample collection but maintains the nucleic acid quality required for diagnostic PCR testing. This inactivation method is needed to alleviate concerns about transmission potential, reduce shipping complications and cost, and allow testing in lower containment laboratories to improve disease diagnostics by improving turn-around time. This study evaluated a panel of ten surrogate viruses that represent highly pathogenic animal diseases. These results showed that a commercial (PrimeStore®) molecular transport media (PSMTM) completely inactivated all viruses tested by >99.99% as determined by infectivity and serial passage assays. However, detection of viral nucleic acid by qRT-PCR was comparable in PSMTM and control-treated conditions. These results were consistent when viruses were evaluated in the presence of biological material such as sera and cloacal swabs to mimic diagnostic sample conditions for non-avian and avian viruses, respectively. The results of this study may be utilized by diagnostic testing laboratories for highly pathogenic agents affecting animal and human populations. These results may be used to revise guidance for select agent diagnostic testing and shipment of infectious substances.